Preparation method of metal organic framework UiO-66 series membrane

The UiO-66 series films were prepared under organic solvent-free conditions by solution impregnation, which solved the problem of the preparation time and the use of organic solvents in the prior art, and achieved efficient and green film preparation and excellent oil-water separation performance.

CN119258812APending Publication Date: 2025-01-07JIANGSU UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411703694.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing UiO-66 series film preparation methods mostly use solvothermal method, using a large amount of organic solvents and taking a long time, lacking a green and environmentally friendly and fast preparation method.

Method used

By solution immersion, the carrier is immersed in Zr4+ ion solution and anchored Zr4+ ions, and then immersed in the organic ligand solution. The UiO-66 crystal film is grown in situ under room temperature to avoid the use of organic solvents, and the use of zirconium sources, adjusters and solvents. A clustered UiO-66 film was formed at a specific ratio and impregnation time.

Benefits of technology

It realizes efficient preparation of UiO-66 series membranes under organic solvent conditions, improves retention and flux, and has good long-term stability and oil-water separation performance, which is suitable for harsh environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119258812A_ABST
    Figure CN119258812A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a metal organic framework UiO-66 series membrane, which comprises the following steps: firstly, dipping a carrier in a solution formed by a zirconium source, a first regulator and a first solvent, so that Zr < 4 + > ions are anchored on the carrier; and dipping the carrier for anchoring Zr < 4 + > in a solution formed by an organic ligand of terephthalic acid or a derivative thereof, a second regulator, a second solvent and water to obtain a membrane material, and cleaning and drying the membrane material to obtain the metal organic framework UiO-66 series membrane. The prepared metal organic framework UiO-66 series membrane is a hydrophilic membrane, water molecules pass through a membrane layer without hindrance, oil molecules are intercepted by the membrane layer, and the metal organic framework UiO-66 series membrane has excellent oil-water separation performance on oil-water emulsion. Experiments show that the retention rate and flux of the UiO-66-NH2 membrane on the normal hexane oil-in-water emulsion are as high as 99.96% and 12.02 * 10 < 4 > L.m <-2 >. H <-1 > respectively.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing an oil-water separation membrane, in particular to a method for preparing a metal organic framework UiO-66 series membrane. Background Art

[0002] Industries such as lubricating oil production and mechanical processing generate a large amount of oily wastewater. The treatment technology of oily wastewater, especially the treatment of oil-water emulsion, has become a hot spot and difficulty in current research. Membrane separation technology has the advantages of low energy consumption and simple operation, and has great market development potential. At present, the most attractive is to use hydrophilic / underwater oleophobic membrane materials, which use the hydrophilic / oleophobic properties of their surface to repel oil pollutants and allow water to pass through.

[0003] The key to the construction of hydrophilic / underwater oleophobic membranes is their surface hydrophilicity and internal microporous structure. On the one hand, through the large number of hydrophilic groups on the membrane surface, it can form hydrogen bonds with water molecules to form a hydrated membrane layer, ensuring a high retention rate. On the other hand, the hydrophilic membrane has a rich microporous structure inside, providing more channels, allowing water molecules to pass through the membrane layer smoothly and obtain a larger flux. UiO-66 (Zr) is a typical metal-organic framework (MOFs) material with common hydrophilic groups (such as -COOH, -OH, -NH2, etc.) and rich microporous structures. It has high water, thermal and chemical stability and is selected as one of the ideal hydrophilic membrane materials. Due to the harsh conditions for the nucleation and growth of UiO-66 crystals and the rigidity of the MOFs crystal membrane itself, the controllable preparation of UiO-66 membranes with both high oil-water separation efficiency and large flux is still a huge challenge.

[0004] Liu et al. used alumina hollow fiber as a carrier and adopted the in-situ growth method at 120°C for 72h to prepare UiO-66 membrane for the first time. Wu et al. dipped the α-Al2O3 hollow tube into the UiO-66 seed / N,N-dimethylformamide dispersion for a few seconds, placed the carrier after seeding into the UiO-66 membrane-forming solution, and prepared UiO-66 membrane by the secondary growth method at 120°C for 72h. Wang et al. first placed the α-Al2O3 hollow tube into the UiO-66-(OH)2 precursor solution at 120°C for 24h to complete the seeding process, and then carried out secondary growth at 120°C for 72h to prepare UiO-66-(OH)2 membrane. Zhang et al. soaked a clean stainless steel mesh in a UiO-66 seed water dispersion at 120°C for 4 hours, and then placed the seeded carrier into a UiO-66 membrane formation solution at room temperature for 18 hours to obtain a UiO-66 stainless steel membrane. Zhu et al. used an in-situ solvothermal method to prepare a super-hydrophilic UiO-66-NH2 membrane using a stainless steel mesh modified with dopamine hydrochloride at 180°C for 12 hours. The oil-water mixture (V油 :V 水 =1:1) and the separation efficiency were 9.03×10 4 L·m -2 ·h -1 and 99.5%. He et al. placed the treated stainless steel mesh into the UiO-66 seed / water dispersion and soaked it at room temperature for 12 hours. Then, the carrier loaded with seed crystals was placed into the UiO-66 film-forming solution at 120°C for 24 hours to obtain an underwater superoleophobic UiO-66 stainless steel membrane. The flux of the chloroform water-in-oil emulsion was as high as 9.0×10 4 L·m -2 ·h -1 , the separation efficiency is close to 100%.

[0005] At present, most UiO-66 series membranes are prepared by solvothermal method, which uses a large amount of DMF organic solvent and is time-consuming. Therefore, a green, environmentally friendly and rapid preparation method for UiO-66 series membranes is urgently needed. Summary of the invention

[0006] Purpose of the invention: The purpose of the present invention is to provide a method for preparing a metal organic framework UiO-66 series membrane which can achieve good separation effect and has a simple process without using an organic solvent.

[0007] Technical solution: The method for preparing the metal organic framework UiO-66 series membrane of the present invention comprises the following steps:

[0008] (1) The support is immersed in a solution formed by a zirconium source, a first adjusting agent and a first solvent so that Zr 4+ The ions are anchored on the carrier;

[0009] (2) Anchor Zr 4+ The ion carrier is immersed in a solution formed by an organic ligand of terephthalic acid or its derivative, a second adjusting agent, a second solvent and water to obtain a membrane material, which is then washed and dried to obtain a metal organic framework UiO-66 series membrane.

[0010] Wherein, in step (1), the molar ratio of the zirconium source: the first adjusting agent: the first solvent is 1:80:170-200, Zr 4+ Maintain sufficient concentration to load enough Zr on the surface of stainless steel carrier 4+ ion.

[0011] Wherein, the immersion time in step (1) is 1 to 2 hours to form Zr 4+ The connection point is combined with the organic ligand in step (2).

[0012] Wherein, in step (1), the zirconium source is at least one of zirconium tetrachloride, zirconium oxychloride, and zirconium n-propoxide.

[0013] Wherein, in step (1), the carrier is a stainless steel mesh of 400, 600 or 800 meshes.

[0014] Wherein, in step (1), the carrier is pretreated by pickling; the pickling process is: soaking the carrier in dilute hydrochloric acid for a period of time, and then soaking, rinsing, and drying the carrier in pure water and ethanol in turn.

[0015] Wherein, in step (2), the molar ratio of the organic ligand: the second adjusting agent: the second solvent: water is 1:80:170-200:200-250; the concentration of the organic ligand and the adjusting agent is ensured to be compatible with Zr 4+ Ions combine to form UiO-66 crystals.

[0016] Wherein, the first adjusting agent and the second adjusting agent are both monocarboxylic acid compounds; preferably formic acid or acetic acid; the first solvent and the second solvent are both ethanol.

[0017] Wherein, the immersion time in step (2) is 2 to 4 hours. If the immersion time is short, UiO-66 grains cannot be generated on the surface of the carrier; if the immersion time is long, more UiO-66 grains may be generated, and the film layer becomes thicker, resulting in a decrease in the emulsion flow rate. Therefore, within this immersion time range, octahedral UiO-66 grains are formed on the surface of the carrier, the interception rate is maintained at a good level, and the flux is greatly improved.

[0018] Wherein, in step (2), the organic ligand of terephthalic acid or its derivative is at least one of terephthalic acid, 2-aminoterephthalic acid, 2-hydroxyterephthalic acid, 2,5-diaminoterephthalic acid or 2,5-dihydroxyterephthalic acid.

[0019] Among them, the UiO-66 series membranes are UiO-66 containing hydrophilic groups, UiO-66-NH2 membranes, UiO-66-OH membranes, UiO-66-(NH2)2 or UiO-66-(OH)2 membranes.

[0020] Principle of the invention: The present invention uses a solution impregnation method to first immerse the carrier in a solution of a Zr source, and then in-situ coat the carrier with Zr. 4+ , and then continue to immerse in the solution of organic ligands, the Zr deposited on the surface of the support 4+ It provides active sites and connection points, combines with organic ligands to grow into UiO-66 crystal membranes. The UiO-66 grains are clustered, avoiding the use of organic solvents, and still achieving higher separation efficiency and larger flux. It has good long-term stability and can be used in harsh environments such as strong acid / strong alkali / high salt / high pressure.

[0021] Beneficial effects: Compared with the prior art, the present invention achieves the following significant effects:

[0022] (1) In the present invention, without using an organic solvent, the carrier is immersed in Zr 4+ Ionic solution and organic ligand solution are added, and the UiO-66 membrane layer with clustered protrusions can be prepared by in-situ growth for several hours at room temperature. It is green and environmentally friendly, with a simple process, a high retention rate, and a greatly improved membrane flux compared to the prior art using organic solvents. (2) The metal organic framework UiO-66 series membrane prepared by the present invention is a hydrophilic / underwater oleophobic membrane, which preferentially adsorbs water with strong polarity. Driven by gravity, water molecules pass through the membrane layer unimpeded, and the water phase is collected on the filtration side. The oil molecules are rejected and retained on the upper side of the membrane layer. It has excellent oil-water separation performance for oil-water mixtures, especially oil-water emulsions. Experiments show that the retention rate and flux of the UiO-66-NH2 membrane for n-hexane water-in-oil emulsion are as high as 99.96% and 12.02×10 4 L·m -2 ·h -1 . BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The SEM images of the surfaces of the UiO-66-NH2 films prepared in Examples 1, 6 and Comparative Example 1;

[0024] Figure 2 The UiO-66-NH2 / 800 mesh stainless steel mesh prepared in Examples 1, 6 and Comparative Example 1 was used to treat the oil-in-water emulsion (V 正己烷 =1.0%) separation performance;

[0025] Figure 3 This is a SEM image of the surface of the UiO-66-NH2 film prepared in Example 1;

[0026] Figure 4 XRD pattern of the UiO-66-NH2 film prepared in Example 1;

[0027] Figure 5 Contact angle test of the UiO-66-NH2 film prepared in Example 1;

[0028] Figure 6 The UiO-66-NH2 / 800 mesh stainless steel mesh prepared in Example 1 was used to treat the oil-in-water emulsion (V 正己烷 =0.2~2.0%) separation performance;

[0029] Figure 7 The long-term stability test of the UiO-66-NH2 / 800 mesh stainless steel mesh prepared in Example 1 (V正己烷 = 1.0% oil-in-water emulsion);

[0030] Figure 8 Acid, alkali and salt stability test of UiO-66-NH2 / 800 mesh stainless steel mesh prepared in Example 1 (V 正己烷 = 1.0% oil-in-water emulsion). DETAILED DESCRIPTION

[0031] The present invention is further described in detail below in conjunction with the accompanying drawings.

[0032] Example 1

[0033] A method for preparing a UiO-66-NH2 film comprises the following steps:

[0034] (1) Carrier pretreatment

[0035] Soak the 400, 600 and 800 mesh stainless steel meshes in dilute hydrochloric acid for 3 hours, soak and rinse them with pure water and ethanol for multiple times, and dry them at 105°C for later use.

[0036] (2) Preparation of UiO-66-NH2 membrane

[0037] The UiO-66-NH2 membrane was prepared by the impregnation method. First, the treated stainless steel mesh was placed in a solution of ZrCl4, formic acid and ethanol and soaked for 1 hour at room temperature, where the amount of ZrCl4: formic acid: ethanol was 1:80:170. 4+ The stainless steel mesh carrier is placed in a solution formed by 2-aminoterephthalic acid, formic acid, ethanol and water, and soaked at room temperature for 2 hours to obtain UiO-66-NH2 membrane material, wherein the amount of 2-aminoterephthalic acid: formic acid: ethanol: water is 1:80:170:220; finally, the UiO-66-NH2 membrane material is soaked and cleaned with anhydrous ethanol several times and dried to obtain the UiO-66-NH2 membrane.

[0038] Depend on Figure 1 It can be seen that octahedral UiO-66 grains are formed on the surface of the UiO-66-NH2 film obtained in this embodiment. Figure 2 The black spheres in the graph represent the retention rate, and the bar graph represents the flux. Figure 2 It can be seen that it has a good separation performance for water-in-oil emulsions, among which V 正己烷 =1.0%. Figure 3 It was observed that the surface of the stainless steel support was covered with clusters of UiO-66-NH2 crystals. Figure 4The XRD spectrum of the UiO-66-NH2 film showed characteristic diffraction peaks of UiO-66-NH2 crystals and stainless steel mesh carrier at 2θ=7.3, 8.5° and 43.6° respectively. Figure 5 It can be seen that through the tests of water contact angle in air and underwater chloroform contact angle, the hydrophilic angle and underwater oil contact angle of UiO-66-NH2 membrane are 42° and 140° respectively, and the membrane is a hydrophilic / underwater oleophobic membrane.

[0039] (3) Gravity separation of oil-in-water emulsions using UiO-66-NH2 membrane

[0040] The n-hexane oil-in-water emulsions with volume ratios of 0.2:99.8, 0.5:99.5, 1:99, 1.5:98.5, and 2:98 were prepared and poured into an oil-water separation device equipped with a UiO-66-NH2 membrane. The rejection rate and flux of the UiO-66-NH2 membrane were as high as 99.96% and (12.02±0.035)×10 4 L·m -2 ·h -1 , see Table 1.

[0041] Depend on Figure 6 to Figure 8 It can be seen that the UiO-66-NH2 membrane can maintain excellent oil-water separation performance under 40 continuous cycles, a wide range of pH values, high salt and high pressure; among them, after 20 cycle tests, it was exposed to the air for 30 days and then tested for oil-water separation performance 20 times; the wide pH value refers to pH 1 and 13, high salt refers to the NaCl mass fraction of 3.5%, and the high pressure value refers to 6 bar.

[0042] Table 1 Separation performance of UiO-66-NH2 membrane for n-hexane oil-in-water emulsion

[0043]

[0044]

[0045] Example 2

[0046] A method for preparing a UiO-66-NH2 film comprises the following steps:

[0047] (1) Carrier pretreatment

[0048] Soak the 400, 600, and 800 mesh stainless steel meshes in dilute hydrochloric acid for 3 hours, soak and rinse them with pure water and ethanol for multiple times, and dry them at 105°C for later use.

[0049] (2) Preparation of UiO-66-NH2 membrane

[0050] The UiO-66-NH2 membrane was prepared by the impregnation method. First, the treated stainless steel mesh was placed in a solution of ZrCl4, acetic acid and ethanol and soaked for 1 hour at room temperature, where the amount of ZrCl4: acetic acid: ethanol was 1:80:170. 4+ The ionic stainless steel mesh carrier is placed in a solution formed by 2-aminoterephthalic acid, acetic acid, ethanol and water, and soaked at room temperature for 2 hours to obtain UiO-66-NH2 membrane material, wherein the amount of 2-aminoterephthalic acid: acetic acid: ethanol: water is 1:80:170:220; finally, the UiO-66-NH2 membrane material is soaked and cleaned with anhydrous ethanol several times and dried to obtain the UiO-66-NH2 membrane.

[0051] (3) Gravity separation of oil-in-water emulsions using UiO-66-NH2 membrane

[0052] N-hexane water-in-oil emulsions with volume ratios of 0.2:99.8, 0.5:99.5, 1:99, 1.5:98.5, and 2:98 were prepared and poured into an oil-water separation device equipped with a UiO-66-NH2 membrane. The retention rate of the UiO-66-NH2 membrane was as high as 99.85%, see Table 2.

[0053] Table 2 Separation performance of UiO-66-NH2 membrane for n-hexane oil-in-water emulsion

[0054]

[0055] Example 3

[0056] A method for preparing a UiO-66-(OH)2 film comprises the following steps:

[0057] (1) Carrier pretreatment

[0058] Soak the 400, 600, and 800 mesh stainless steel meshes in dilute hydrochloric acid for 3 hours, soak and rinse them with pure water and ethanol for multiple times, and dry them at 105°C for later use.

[0059] (2) Preparation of UiO-66-(OH)2 membrane

[0060] The UiO-66-(OH)2 membrane was prepared by the impregnation method. First, the treated stainless steel mesh was placed in a solution of ZrCl4, formic acid and ethanol and soaked for 1 hour at room temperature, where the amount of ZrCl4: formic acid: ethanol was 1:80:172. 4+The ionic stainless steel mesh carrier is placed in a solution formed by 2,5-dihydroxyterephthalic acid, formic acid, ethanol and water, and soaked at room temperature for 2 hours to obtain UiO-66-(OH)2 membrane material, wherein the amount of 2,5-dihydroxyterephthalic acid: formic acid: ethanol: water is 1:80:172:220; finally, the UiO-66-(OH)2 membrane material is soaked and cleaned several times with anhydrous ethanol and dried to obtain the UiO-66-(OH)2 membrane.

[0061] (4) Gravity separation of oil-in-water emulsions using UiO-66-(OH)2 membranes

[0062] N-hexane water-in-oil emulsions with volume ratios of 0.2:99.8, 0.5:99.5, 1:99, 1.5:98.5, and 2:98 were prepared and poured into an oil-water separation device equipped with a UiO-66-(OH)2 membrane. The retention rate of the UiO-66-(OH)2 membrane was as high as 95.46%, as shown in Table 3.

[0063] Table 3 Separation performance of UiO-66-(OH)2 membrane for n-hexane oil-in-water emulsion

[0064]

[0065] Example 4

[0066] Compared with Example 1, the difference is that the amount of ZrCl4:formic acid:ethanol is 1:80:200.

[0067] Example 5

[0068] Compared with Example 1, the difference is that the amount of substance of 2-aminoterephthalic acid:formic acid:ethanol:water is 1:80:200:250.

[0069] Example 6

[0070] Compared with Example 1, the difference is that in step (2), the anchoring Zr 4+ The stainless steel mesh carrier is placed in a solution formed by 2-aminoterephthalic acid, formic acid, ethanol and water, and the soaking time at room temperature is set to 4 hours.

[0071] Comparative Example 1

[0072] Compared with Example 1, the difference is that in step (2), the anchoring Zr 4+ The stainless steel mesh carrier was placed in a solution formed by 2-aminoterephthalic acid, formic acid, ethanol and water, and the soaking time at room temperature was set to 0.5h, 1h, 1.5h, 8h and 12h respectively.

[0073] When anchored Zr 4+When the ion-containing stainless steel mesh carrier is immersed in a solution of 2-aminoterephthalic acid, formic acid, ethanol and water for too short a time, such as 0.5h, 1h and 1.5h respectively, UiO-66 grains cannot be generated on the carrier surface. The SEM images of the UiO-66 grains obtained by immersion for 0.5h and 1h are as follows: Figure 1 As shown; and at this time, the separation performance of the water-in-oil emulsion (Vn-hexane = 1.0%) is also poor; if the immersion time is too long, such as 8h and 12h, the emulsion flow rate decreases due to the large number of UiO-66 crystals generated and the thicker membrane layer, as shown in FIG. Figure 2 shown.

Claims

1. A method for preparing a metal organic framework UiO-66 series membrane, characterized in that: The following steps are involved: (1) The support is immersed in a solution formed by a zirconium source, a first adjusting agent and a first solvent so that Zr 4+ The ions are anchored on the carrier; (2) Anchor Zr 4+ The ion carrier is immersed in a solution formed by an organic ligand of terephthalic acid or its derivative, a second adjusting agent, a second solvent and water to obtain a membrane material, which is then washed and dried to obtain a metal organic framework UiO-66 series membrane.

2. The method for preparing the metal organic framework UiO-66 series membrane according to claim 1, characterized in that: In step (1), the molar ratio of the zirconium source: the first adjusting agent: the first solvent is 1:80:170-200.

3. The method for preparing the metal organic framework UiO-66 series membrane according to claim 1, characterized in that: In step (2), the molar ratio of the organic ligand: the second adjusting agent: the second solvent: water is 1:80:170-200:200-250.

4. The method for preparing the metal organic framework UiO-66 series membrane according to claim 1, characterized in that: The immersion time in step (1) is 1 to 2 hours; the immersion time in step (2) is 2 to 4 hours.

5. The method for preparing the metal organic framework UiO-66 series membrane according to claim 1, characterized in that: The first adjusting agent and the second adjusting agent are both monocarboxylic acid compounds.

6. The method for preparing the metal organic framework UiO-66 series membrane according to claim 1, characterized in that: In step (2), the organic ligand of terephthalic acid or its derivative is at least one of terephthalic acid, 2-aminoterephthalic acid, 2-hydroxyterephthalic acid, 2,5-diaminoterephthalic acid or 2,5-dihydroxyterephthalic acid.

7. The method for preparing the metal organic framework UiO-66 series membrane according to claim 1, characterized in that: In step (1), the zirconium source is at least one of zirconium tetrachloride, zirconium oxychloride, and zirconium n-propoxide.

8. The method for preparing the metal organic framework UiO-66 series membrane according to claim 1, characterized in that: In step (1), the carrier is a stainless steel mesh of 400, 600 or 800 meshes.

9. The method for preparing the metal organic framework UiO-66 series membrane according to claim 1, characterized in that: In step (1), the carrier is pretreated by acid washing.

10. The method for preparing the metal organic framework UiO-66 series membrane according to claim 1, characterized in that: The UiO-66 series membranes are UiO-66 containing hydrophilic groups, UiO-66-NH2 membranes, UiO-66-OH membranes, UiO-66-(NH2)2 or UiO-66-(OH)2 membranes.